Lentinan inhibits oxidative stress and inflammatory cytokine production induced by benzo(a)pyrene in human keratinocytes. (28th May 2019) - Zi, Yusha; Jiang, Biao; He, Congfen; Liu, Lei
Abstract: Background: Benzo(a)pyrene, a major environmental pollutant, is known to accelerate skin aging through oxidative stress, increase the production of inflammatory mediators, and cause skin cancer. Lentinan, prepared from Lentinus edodes (Shiitake mushroom), has been reported to exhibit anti‐coagulant, anti‐viral, anti‐cancer, anti‐tumor, and anti‐coagulant effects. However, the effect of lentinan on human keratinocytes treated with benzo(a)pyrene is unknown. Aims: The aim of this study was to explore whether lentinan inhibits benzo(a)pyrene‐induced oxidative stress and inflammatory cytokine production in human keratinocytes. Methods: We investigated the effect of lentinan on benzo(a)pyrene‐induced oxidative stress indicators (malondialdehyde, superoxide dismutase, and glutathione peroxidase) in human immortalized keratinocytes (HaCaT cells). We also assessed the production of inflammatory factors interleukin‐8 and chemokine ligand‐2 induced by benzo(a)pyrene exposure at both mRNA and protein levels. Results: Lentinan inhibited oxidative stress induced by benzo(a)pyrene, as shown by the concentration‐dependent reduction in reactive oxygen species in HaCaT cells. In addition, malondialdehyde levels were reduced to 53% of those of cells treated with benzo(a)pyrene without lentinan. The activities of superoxide dismutase and glutathione peroxidase were approximately 18‐ and 2.7‐fold higher in benzo(a)pyrene‐treated cells with lentinan than in those without lentinan. Moreover, lentinan significantly reduced interleukin‐8 and chemokine ligand‐2 mRNA and protein levels. Conclusions: These findings suggest that lentinan has two biological activities that are potentially useful for managing inflammatory skin diseases or disorders related to oxidative stress induced by benzo(a)pyrene. Therefore, cosmetics containing L edodes have promising dermatological applications, with potential utility in protecting the skin against environmental pollutants.